Development of Emergency System of Power Grids with a Significant Renewable Generation - Stognii, B.S.; Kyrylenko, O.V.; Pavlovsky, V.V.; Sopel, M.F.; Steliuk, A.O.; Lukianenko, L.M. (Science and Innovation, 2024)
The need for the development of adaptive emergency system of the power grid with a significant renewable generation has been substantiated. The main stages of the system development have been presented that enables to define settings of the emergency systems considering the features of the renewables, as well as to develop the system, which has been implemented for the power grids of Odesa Oblast.